Stones before Touching the Sharpen Knives - Bello, OO; Morhason-Bello, IO; Lawal, OO; Abduls-Salam, RA; Babawarun, TO; Ojengbede, AO (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess the effectiveness of training in fistula repair. Methods: A semi structured self-administered questionnaire was used to elicit responses from seven fistula surgeon trainees who trained for standard level of fistula repair during 2014-2018. Data analysis was done using SPSS 20.0. Results: The mean age and duration of medical practice of participants was 41.6 years (SD=5.6) and 14.9 years (SD=6.9) respectively. Almost all trainees were male 6 (85.7%) and five had postgraduate fellowships. Only one trainee (14.3%) had received previous formal training in fistula repair while four (57.1%) had previously done a surgical repair. All trainees participated and assisted in surgical repairs while 6 (85.7%) were the lead surgeon in at least 3 surgeries during training. Following training, four (57.1%) trainees witnessed an increase in the number of fistula patients presenting at their health facilities. Five trainees (71.4%) saw fistula cases that were beyond the level of their training. All trainees reported an increase in proficiency in fistula repair evidenced by successful outcomes of about 80% at first attempt. Lack of adequate infrastructural, personnel and social support for patients during and post training were cited by all trainees as barriers to the provision of adequate care for fistula repair. Conclusions: There is need for more commitment to training so as to address the treatment gap and eliminate the backlog of unrepaired fistula cases.